Factors Affecting Nurses for Doing Therapeutic Communication Therapy to Clients at Mon Geudong Puskesmas Lhokseumawe - Dedy Ahmady; Luqman (Jurnal Kesehatan Akimal, 2021)
Therapeutic communication is a verbal exchange that is consciously planned, purposeful, and that activities are centered on the healing of the client. The objective of this study is to describe the factors that influence nurses to communicate therapeutically to clients at the Mon Geudong Public Health Center, Lhokseumawe City. This is analytic research with a cross-sectional design. The Respondents in this study amounted to 43 civil servant nurses (total sample). The results obtained between the factors that influence therapeutic communication from 43 respondents, 29 respondents (67.4%) are in the "Good" category and 14 respondents (32.6%) are in the "Not Good" category. According to the knowledge variable, which is from 43 respondents and 27 respondents (62.8%) were answered "yes", and 16 respondents (37.2%) were answered "No", while the environmental variables of 43 respondents were 24 people rrespondents (55.8%) are answered â€œYesâ€ and 19 respondents (44.2%) are answered â€œNoâ€. The perception variable of 43 respondents and 27 respondents (62.8%) is in the â€œYesâ€ category and 16 respondents (37.2%) are in the â€œNoâ€ category. The relationship between knowledge, environment, and perception with therapeutic communication obtained p-value = 0.005 <: 0.05, there is indicated a significant relationship between knowledge, environment, and perception with therapeutic communication. Finally, the results concluded that three variables are very influential on nurses in conducting therapeutic communication.